Pannexin-1 channel opening is critical for COVID-19 pathogenesis - Ross Luu; Silvana Valdebenito; Eliana Scemes; Antonio Cibelli; David C. Spray; Maximiliano Rovegno; Juan Tichauer; Andrea Cottignies-Calamarte; Arielle Rosenberg; Calude Capron; Sandrine Belouzard; Jean Dubuisson; et al. (iScience, 2021)
Summary: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rapidly rampaged worldwide, causing a pandemic of coronavirus disease (COVID -19), but the biology of SARS-CoV-2 remains under investigation. We demonstrate that both SARS-CoV-2 spike protein and human coronavirus 229E (hCoV-229E) or its purified S protein, one of the main viruses responsible for the common cold, induce the transient opening of Pannexin-1 (Panx-1) channels in human lung epithelial cells. However, the Panx-1 channel opening induced by SARS-CoV-2 is greater and more prolonged than hCoV-229E/S protein, resulting in an enhanced ATP, PGE2, and IL-1β release. Analysis of lung lavages and tissues indicate that Panx-1 mRNA expression is associated with increased ATP, PGE2, and IL-1β levels. Panx-1 channel opening induced by SARS-CoV-2 spike protein is angiotensin-converting enzyme 2 (ACE-2), endocytosis, and furin dependent. Overall, we demonstrated that Panx-1 channel is a critical contributor to SARS-CoV-2 infection and should be considered as an alternative therapy.